Calibration of a burrow count index for the Indian desert jird, Meriones hurrianae. Issue 1 (9th September 2012) - Ramesh, Divya; Home, Chandrima; Jhala, Yadvendradev V.; Qureshi, Qamar
Abstract: Population estimates, often difficult to acquire, warrantee the use of an index as an economical substitute for rapid assessments of populations. We estimated population size of the little known social, semi‐fossorial Indian desert jird ( Meriones hurrianae ) in Kachchh, Gujarat, India under closed population capture‐mark‐recapture (CMR) framework to calibrate a burrow count index for the species. A total of 147 individuals were trapped in 16 colonies using baited Sherman traps and the number of burrow entrances at each colony was recorded. Data from colonies with low number of captures were pooled to estimate capture probability using Huggins heterogeneity models with gender, site, body weight and age category as covariates in Program MARK. Colony sizes ranged from 2 to 46 individuals. The number of burrow entrances was calibrated against CMR‐based population estimates using least squares regression ( n = 16, adjusted R 2 = 0.96, t = 18.18, P < 0.001). The index was further validated using Jackknife (JK) analysis where JK‐predicted population estimates strongly correlated with CMR estimates ( r = 0.96, P < 0.001). In habitats and climatic conditions similar to Kachchh and within the range of colony sizes sampled, our calibrated index can be a valuable and effective tool for large scale surveys of the desert jird, which occupies a keystone trophic level in the semi‐arid ecosystem.